Acid-Catalyzed Intramolecular Ring-Opening Reactions of Cyclopropanated Oxabenzonorbornadienes with Carboxylic Acid Nucleophiles - Ho, Angel; Pounder, Austin; Koh, Samuel; Macleod, Matthew P.; Carlson, Emily; Tam, William (Synthesis, 2021)
The present work demonstrates the ability of carboxylic acid tethered cyclopropanated oxabenzonorbornadienes (CPOBDs) to undergo ring-opening reactions in mild acidic conditions. The optimized reaction conditions involve the use of pTsOH in DCE at 90 °C. Two regioisomers are formed but the reactions are highly regioselective towards type 3 ring-opened products. It was observed that substitution at the C5 and aryl positions of CPOBD significantly hinders the ring-opening reactions leading to decreased yields of ring-opened products, although high regioselectivity for the Type 3 ring-opened products is still maintained. Herein, the first examples of acid-catalyzed intramolecular ring-opening reactions of CPOBD with carboxylic acid nucleophiles are reported.
Keywords: oxabenzonorbornadiene; cyclopropanated oxabenzonorbornadiene; intramolecular; nucleophilic ring-opening; acid-catalysis